The history of Italy - Killinger, Charles L. (Greenwood histories of the modern nations., 2002)
The most current account of the richly complex and critically important history of Italy from the Romans to the height of the Renaissance, and from the long struggle for unification to the second world war and post war economic success. What is Italy? In 1814 Austrian Chancellor M. de Metternich dismissed it as a mere "geographical expression." He could say so because political control of the peninsula had for centuries been divided among self-governing cities, possessions of foreign dynasties, and the Vatican. Prior to that Italy formed the "home base" of the Roman Empire. It was not until 1861, however, that a united Italy emerged. This concise, and clearly written account explores Italian history and culture from the Etruscans up to the present day. Along the way readers will discover the Romans, Lombards, popes, Guelphs, Ghibellines, the Medici, the Risorgimento, sculptors, composers, Fascists, Christian Democrats, and many other people and events that make up the rich heritage of Italian history. The History of Italy is succinct, complete, and the most up-to-date general history of the nation available.; Starting with an introduction providing data on Italy's geography, people, and current government, the book then examines the political and cultural history of the country in eleven chapters. Also included is a biographical section with portraits of noteworthy Italians, an extensive bibliographical essay, a glossary of terms, and an index